Comprehensive cyber security for port and harbor ecosystems - Pöyhönen, Jouni; Lehto, Martti (Frontiers in Computer Science, 2023)
Global maritime transportation and logistics systems are essential parts of critical infrastructures in every society, and a crucial part of maritime logistics processes are seaports. In the coming years, digitalization and increased levels of autonomy in logistic transport chains are expected to take leaps forward. This development can help create safer, more efficient, more sustainable, and more reliable service chains to meet the requirements for a better quality of life and global prosperity. Port and harbor operations connect the maritime transport to other modes of transportation and enable multimodal transportation. Smart ports play in a central role in future transport logistics and supply chains. Digitalization helps improve the efficiency of terminal systems in the processes of these ports. In the best cases, digitalization can also promote the reduction of emissions by optimizing port operations and enhancing cargo and people flows while improving the experience for all stakeholders. The improvement of port processes relies on the development of information and communication technology (ICT) as well as on industrial control systems (ICS) and operation technologies (OT). At the same time, the cyber security of maritime logistics also needs to be addressed. This article presents our findings related to the Sea4Value research goal on cyber security, which is a comprehensive cyber security architecture for port services at the system level. The article emphasizes the importance of a system of systems approach in terms of a comprehensive cyber security management process for port ecosystems. The description and recognition of management steps of every stakeholder are the key elements in this kind of process.